Epistemic Words on the Confidence Scale - Ніжнік, Людмила; Бялик, Василь Дмитрович (Academic Journal of Modern Philology, 2022)
The article examines a group of 107 epistemic words in order to determine their integral and differential semes and place them on the confidence scale. The relevance of the study is conditioned by the interest in studying the stance of a speaker’s utterance. The article analyses the notion of epistemic words, their linguistic and non-linguistic properties. As a result of definition and semantic analyses of epistemic words, epistemic words with high, medium and low modal strength were singled out. Such a categorization is possible, because epistemic words have the same integral semes but various differential semes. Epistemic words have a scalar nature and the level of their modal strength reflects the speaker’s commitment to the utterance that ranges from confidence to uncertainty.
Keywords: epistemic words; confidence scale; modal strength; component analysis